Organic luminescent compound and organic electroluminescent device thereof

By designing a specific organic luminescent compound and optimizing its energy level structure and stability, the problem of low luminescent efficiency of OLED devices under high current density is solved, and higher luminescent efficiency and stability are achieved.

CN119661546AInactive Publication Date: 2025-03-21西安欧得光电材料有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510203450.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing organic light emitting diode (OLED) devices have problems with carrier transmission mismatch and charge recombination area limitations under high current density, resulting in low luminous efficiency.

Method used

Using a new organic luminescent compound whose structure is specific to the combination of X1, X2, X3, X4, Y, R1, R3, R2 and n, the energy level structure and stability of the molecule are optimized by introducing electron donor units and electron acceptor units, as well as a construction unit with large steric hindrance.

Benefits of technology

The energy gap value between the S1 state and the T1 state of the organic luminescent compound is small, and the exciton lifetime of the T1 state is long. It can achieve the transformation of T1→S1 through reverse intersystem crossing, improve the luminescence efficiency and stability, and effectively balance the transmission of carriers, reducing the quenching of the triplet-tritt state under high exciton concentration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661546A_ABST
    Figure CN119661546A_ABST
Patent Text Reader

Abstract

The invention discloses an organic light-emitting compound and an organic electroluminescent device thereof, the compound is used as a bipolar main body material, and an electron donor unit D (Donat), an electron acceptor unit A (Aceppt) and a large steric hindrance construction unit are introduced, so that the transmission of current carriers can be effectively balanced, excitons can be uniformly distributed, and the light-emitting efficiency is improved. The recombination of carriers at an interface is avoided, and the quenching of triplet state-triplet state under high exciton concentration is reduced, so that the performance and the stability of the device are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of organic electroluminescent materials, and in particular relates to an organic luminescent compound and an organic electroluminescent device thereof. Background Art

[0002] The design of organic light-emitting diode (OLED) devices usually adopts a complex multi-layer structure, which includes a hole injection layer, a hole transport layer, an electron injection layer, an electron transport layer, and the most critical light-emitting layer. The light-emitting layer is composed of a host material and a guest material (i.e., a dopant). Sometimes, a sensitizer is added to further optimize the energy level matching and improve the luminous efficiency. In this structure, the selection of the host material is crucial. It must have high stability and a suitable energy level structure to ensure efficient energy transfer and effectively avoid the annihilation of high-concentration excitons.

[0003] At present, the host materials on the market can be roughly divided into three categories: hole transport type, electron transport type and bipolar transport material. Different types of host materials will form charge recombination zones at specific layer interfaces, but this also brings about problems of carrier mobility mismatch and charge recombination area limitation, thus affecting the luminescence efficiency. Especially at high current density, triplet annihilation will accelerate, further reducing the luminescence efficiency. To solve these problems, the industry usually adopts the strategy of double emitting layers or mixed host materials, but these methods not only increase the complexity of preparation, but may also cause phase separation problems.

[0004] Bipolar host materials have shown unique advantages in the field of OLEDs because they can balance the transmission of holes and electrons and simplify the device structure. However, the development of bipolar materials with wide energy level distribution in the market is still insufficient and cannot meet the growing market demand. Therefore, the development of higher performance organic light-emitting compounds has become a top priority. Summary of the invention

[0005] The purpose of the present invention is to overcome the above-mentioned deficiencies of the prior art and provide an organic light-emitting compound and an organic electroluminescent device thereof.

[0006] In order to solve the technical problem, the technical solution of the present invention is: An organic light-emitting compound, wherein the organic light-emitting compound has a structure as shown in Formula 1: ; Where: X 1 , X 2 , X 3 , X 4 Each is independently selected from a N atom or a C atom and satisfies the following conditions: When X 1 and X 3When both are N atoms, X 2 and X 4 Must be a C atom; When X 2 and X 4 When both are N atoms, X 1 and X 3 Must be a C atom; When X 1 and X 3 When X 2 and X 4 When they are not N atoms at the same time, X 1 , X 2 , X 3 , X 4 The combination of is any combination of N atoms and C atoms; Y is selected from an O atom or a S atom; R 1 and R 3 are each independently selected from any one of C6 to C12 aromatic groups, and R 1 , R 3 The bonding mode with the main structure is ring bonding, R 1 and the aryl group in R3 is a monocyclic aryl group or a polycyclic aryl group; R 2 Any one selected from C6-C30 aryl and C4-C30 heteroaryl, R 2 The bonding mode with the main structure is a single bond; R 2 The heteroaryl group includes a monocyclic heteroaryl group, a polycyclic heteroaryl group or a condensed-ring heteroaryl group, and the heteroatom in the heteroaryl group includes but is not limited to an O atom, a S atom or a N atom; n is selected from 0, 1, 2 or 3.

[0007] Preferably, the R 2 Selected from the following groups L 1 ~L 42 or any of its derivatives: , in, For R 2 Bonding position to the main structure.

[0008] Preferably, the organic light-emitting compound is any one of the following compounds 1 to 224, and the specific structural formula is as follows: .

[0009] An organic electroluminescent device, comprising a cathode, an anode and an organic layer between the cathode and the anode, wherein the organic layer comprises a hole transport layer, a light emitting layer and an electron transport layer, wherein the light emitting layer comprises a host light emitting material and a guest light emitting material, wherein the host light emitting material comprises any one or a combination of two of the organic light emitting compounds described in the present invention. Preferably, the guest light emitting material can be selected from phosphorescent materials with excellent performance. , and the mass fraction of the guest luminescent material in the entire luminescent layer is between 0.1% and 3.0%.

[0010] Preferably, the guest luminescent material can also be selected from fluorescent materials with excellent performance. , and the mass fraction of the guest luminescent material in the entire luminescent layer is between 0.5% and 5.0%.

[0011] Preferably, the organic electroluminescent device is used in the fields of luminous lighting, image display or optoelectronic signal transmission.

[0012] Compared with the prior art, the advantages of the present invention are: (1) The organic light-emitting compounds of the present invention can be used as bipolar host materials. 1 State and T 1 The energy gap between the states is small and T 1 When the lifetime of the exciton is long, under certain temperature conditions, T 1 The excitons can realize T through reverse intersystem crossing (RISC). 1 →S 1 The transformation of S 1 The radiative decay of the state to the ground state S 0 ,This process helps to improve the luminous efficiency and stability; (2) The organic light-emitting compound of the present invention introduces an electron donor unit D (Donat) and an electron acceptor unit A (Aceppt) as well as a building unit with large steric hindrance. This design not only achieves efficient control of the LUMO and HOMO energy levels of the molecule, but also enhances the structural stability of the molecule and effectively regulates the internal energy level distribution of the molecule, thereby optimizing the luminescence performance; (3) The organic light-emitting compound of the present invention is used as a bipolar host material in the light-emitting layer of an OLED device, which can effectively balance the transmission of carriers, thereby enabling the excitons to be evenly distributed, avoiding the recombination of carriers at the interface, and reducing the triplet-triplet quenching under high exciton concentration, thereby improving the performance and stability of the device; (4) The organic functional layer based on the bipolar host material of the present invention can make the structure of the OLED device simpler, thereby reducing the preparation cost and complexity; (5) The organic light-emitting compound of the present invention is very suitable for use as a host material of a phosphorescent material or a fluorescent material, providing more options and flexibility for the design of OLED devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 , a cross-sectional view of an organic electroluminescent device of the present invention; Figure 2 , the NMR spectrum of compound 2 of the present invention; Figure 3 , the NMR spectrum of compound 33 of the present invention; Description of reference numerals: 1. polymer substrate, 2. anode layer, 3. hole injection layer, 4. hole transport layer, 5. electron blocking layer, 6. light-emitting layer, 7. hole blocking layer, 8. electron transport layer, 9. electron injection layer, 10. cathode layer, 11. covering layer. DETAILED DESCRIPTION

[0014] The present invention is described below in conjunction with specific examples. The raw materials, solvents and catalysts used are all conventional commercially available products. The following examples are used to illustrate the present invention but are not intended to limit the scope of the present invention.

[0015] The synthesis process of the organic light-emitting compound of the present invention is specifically described as follows: The key intermediate structures involved in the present invention are shown in Table 1.

[0016] Table 1 Key intermediate structures involved in the present invention

[0017] Synthesis process of intermediate M1:

[0018] Step 1: Synthesis of M1-1: Operation process: Under nitrogen protection, N-(8-bromobenzonaphthyl-9-yl)acetamide (314 g, 1.0 mol), o-methoxyphenylboronic acid (182 g, 1.2 mol), 4 L THF, 1 L H 2 O.K 2 CO 3 (415 g, 3.0 mol), heated to 40 °C with stirring, and after the solution was clarified, Pd(PPh 3 ) 4 (35g, 0.03mol), after the addition, the reaction solution was heated to 80°C and the reaction was continued for 12h. After the reaction was completed, diatomaceous earth was used to filter while hot, the filtrate was cooled to room temperature, the solution was concentrated, 5L of ethyl acetate and 5L of water were added for extraction, the organic phase was dried over anhydrous magnesium sulfate, filtered and concentrated, and the residue was purified by silica gel column chromatography (dichloromethane / petroleum ether heavy) to obtain M1-1, with a yield of 273g, a yield of 80%, an HPLC content of 98%, and a molecular weight of 342.1 shown by LC-MS.

[0019] Step 2: Synthesis of M1-2: Operation process: Under nitrogen protection, M1-1 (273g, 0.8mol) and 3.0L of dichloromethane were added to a 10L three-necked flask in sequence, stirring was started, and the temperature was cooled to 0°C in an ice-salt bath. 0.92L of dichloromethane solution of boron tribromide (1.0mol / L) was dropped into the system. After the addition was completed, the reaction solution was heated to room temperature and reacted for 18h. After the reaction was completed, the reaction solution was cooled to 0°C and 100mL of ice water was slowly added to quench. Saturated sodium bicarbonate solution (0.5L) was added dropwise until the reaction solution was weakly alkaline. The organic phase was separated and washed with small amounts of water several times until neutral. The organic phase was dried and concentrated under reduced pressure. The residue was recrystallized from dichloromethane / petroleum ether to obtain M1-2 with a yield of 230g and a yield of 88%. The HPLC content was 98%, and the LC-MS showed a molecular weight of 328.1.

[0020] Step 3: Synthesis of M1: Operation process: Under nitrogen protection, add M1-2 (229g, 0.7mol) to a 5L three-necked flask in sequence, add 1.5L of 95% ethanol, and 0.9L of 80% hydrazine hydrate, start stirring, and heat the reaction liquid to reflux temperature. Continue the reaction for 40 hours until the reaction is complete. After the reaction is completed, the reaction liquid is cooled to room temperature, 5L of dichloromethane is added for extraction, the organic phase is dried and concentrated, and the residue is purified by silica gel column to obtain M1, with a yield of 174g, a yield of 93%, an HPLC content of 98%, and a molecular weight of 268.0 shown by LC-MS.

[0021] Synthesis process of intermediate M2:

[0022] Step 1: Synthesis of M2-1: Operation process: Under nitrogen protection, add M1 (174g, 0.65mol), p-chlorobromobenzene (124g, 0.65mol), and 2.0L toluene in a 5L three-necked flask in sequence, stir until the solution is clear, and add Pd 2 (dba) 3 (12g, 0.013mol), Am-Phos (7g, 0.0325mol), sodium tert-butoxide (125g, 1.3mol), the reaction solution was heated to reflux temperature, and the reaction was continued for 10h until the reaction was complete. Filtered with diatomaceous earth while hot, the filtrate was cooled to room temperature, and purified water was added for washing. After separation, the organic phase was retained, and the aqueous phase was extracted with 6L ethyl acetate for 3 times, each time with 2L, and the organic phases were combined, dried over anhydrous magnesium sulfate, and concentrated. The residue was purified by silica gel column chromatography to obtain M2-1, with a yield of 201g, a yield of 82%, an HPLC content of 98%, and a molecular weight of 378.1 shown by LC-MS.

[0023] Step 2: Synthesis of M2: Operation process: Under nitrogen protection, add M2-1 (189g, 0.5mol), bipyralidone (152g, 0.6mol), potassium acetate (108g, 1.1mol), 2.5L of 1,4-dioxane into a 5L three-necked flask in sequence, start stirring, heat to 65℃, and then add Pd(dppf)Cl 2 (4.1g, 5mol), the reaction solution was heated to reflux temperature, and the reaction was continued for 8h until the reaction was complete. The reaction solution was directly filtered, the filtrate was collected, concentrated under reduced pressure, dissolved in 1500mL toluene, washed with water, separated, the organic phase was dried and concentrated, the residue was purified by silica gel column chromatography (dichloromethane / petroleum ether), the column liquid was concentrated under reduced pressure again until solids precipitated, the concentration was stopped, the system was cooled to 10~15℃, after crystallization was completed, filtered, and dried to obtain M2, with a yield of 185g, a yield of 79%, an HPLC content of 99%, and a molecular weight of 470.2 shown by LC-MS.

[0024] Synthesis process of intermediate M3:

[0025] Step 1: Synthesis of M3-1: Operation process: Under nitrogen protection, 3-bromonaphthalene-2-amine (222 g, 1.0 mol), (8-chloronaphthalene-1-yl)boric acid (206 g, 1.0 mol), potassium carbonate (K 2 CO 3) (415g, 3.0mol), 4.0L THF, 1.0L water, Pd(t-Bu 3 P) 2 (15g, 0.03mol), stirring was started, the reaction solution was heated to 80°C, and the reaction was continued for 12h until the reaction was completed. The reaction solution was directly filtered, the filtrate was collected, and the organic solvent was removed by vacuum concentration. 5L chloroform and 5L water were added to the system for washing, and the liquid was separated. The organic phase was dried over anhydrous magnesium sulfate, filtered, and concentrated. The residue was purified by silica gel column chromatography to obtain intermediate M3-1, with a yield of 231g, a yield of 76%, an HPLC content of 98%, and an LC-MS molecular weight of 304.0.

[0026] Step 2: Synthesis of M3: Operation process: Under nitrogen protection, M3-1 (228 g, 0.75 mol), sodium tert-butoxide (216 g, 2.25 mol), Pd(t-Bu 3 P) 2 (11.5g, 0.023mol), 5.0L of xylene, stirring was started, the reaction solution was heated to reflux temperature, and the reaction was continued for 2h until the reaction was complete. The reaction solution was directly filtered, the filtrate was collected, and the solvent was removed by concentration under reduced pressure. 5L of chloroform and 5L of water were added to the system, washed, separated, the organic phase was dried with anhydrous magnesium sulfate, filtered, concentrated, and the residue was recrystallized with dichloromethane / petroleum ether to obtain intermediate M3, with a yield of 138g, a yield of 69%, an HPLC content of 99%, and an LC-MS molecular weight of 268.0.

[0027] Synthesis process of intermediate M4:

[0028] Step 1: Synthesis of M4-1: Operation process: The synthesis process of M4-1 refers to the synthesis process of M2-1. M3 (134 g, 0.5 mol) and p-chlorobromobenzene (96 g, 0.5 mol) are added to obtain M4-1 with a yield of 153 g, a yield of 81%, a HPLC content of 98%, and a LC-MS molecular weight of 378.0.

[0029] Step 2: Synthesis of M4: Operation process: The synthesis process of M4 refers to the synthesis process of M2. M4-1 (151 g, 0.4 mol) was added to obtain M4 with a yield of 143 g, a yield of 76%, a HPLC content of 99%, and a LC-MS molecular weight of 470.1.

[0030] Synthesis of intermediate M5:

[0031] Step 1: Synthesis of M5-1: Operation process: Under nitrogen protection, 2,4-dichlorobenzofuran[3,2-D]pyrimidine (24 g, 0.1 mol), M1 (27 g, 0.1 mol), Pd 2 (dba) 3 (1.8 g, 2 mmol), P(t-Bu) 3 (1.0g, 5mmol), sodium tert-butoxide (19g, 0.2mol), toluene 200mL, stirring was started, the reaction solution was heated to reflux temperature, and the reaction was continued for 8h until the reaction was complete. The reaction solution was cooled to room temperature, filtered, the filtrate was washed with water, separated, the organic phase was dried, filtered and concentrated, and the residue was purified by silica gel column chromatography to obtain M5-1, with a yield of 29g, a yield of 61%, an HPLC content of 99%, and an LC-MS molecular weight of 470.1.

[0032] Step 2: Synthesis of M5: Operation process: The synthesis process of M5 refers to the synthesis process of M2. M5-1 (29 g, 0.06 mol) was added to obtain M5 with a yield of 26 g, a yield of 75%, a HPLC content of 99%, and a LC-MS molecular weight of 562.2.

[0033] Synthesis of intermediate M7:

[0034] Step 1: Synthesis of M7-1: Operation process: The synthesis process of M7-1 refers to the synthesis process of M5. 2,4-dichloro-benzofuran[2,3-d]pyrimidine (24 g, 0.1 mol) and M1 (27 g, 0.1 mol) were added to obtain M7-1 with a yield of 29 g, a yield of 62%, a HPLC content of 99%, and a LC-MS molecular weight of 470.1.

[0035] Step 2: Synthesis of M7: Operation process: The synthesis process of M7 refers to the synthesis process of M2. M7-1 (29 g, 0.06 mol) was added to obtain M7 with a yield of 26 g, a yield of 74%, a HPLC content of 99%, and a LC-MS molecular weight of 562.2.

[0036] Synthesis of intermediate M9:

[0037] Step 1: Synthesis of M9-1: Operation process: Under nitrogen protection, 2,4-dichlorobenzofuran[3,2-D]pyrimidine (24 g, 0.1 mol), M2 (47 g, 0.1 mol), 200 mL THF, 50 mL H2 O, K 2 CO 3 (41 g, 0.3 mol), heated to 40 °C with stirring, and after the solution was clarified, Pd(PPh 3 ) 4 (3.5 g, 3 mmol), stirring was started, the reaction solution was heated to 80 ° C, and the reaction was continued for 12 h until the reaction was completed. THF was distilled under reduced pressure, 0.5 L of water was added to the system, and the mixed solution was extracted with 3 L of ethyl acetate for 3 times, each time with 1 L, the organic phases were combined, the organic phases were dried and concentrated, and the residue was purified by silica gel column chromatography to obtain M9-1, with a yield of 42 g, a yield of 77%, an HPLC content of 98%, and a molecular weight of 546.1 shown by LC-MS.

[0038] Step 2: Synthesis of M9: Operation process: The synthesis process of M9 refers to the synthesis process of M2. M9-1 (42 g, 0.08 mol) was added to obtain M9 with a yield of 37 g, a yield of 76%, a HPLC content of 99%, and a LC-MS molecular weight of 638.3.

[0039] Synthesis of intermediate M13:

[0040] Step 1 Synthesis of M13-1: Operation process: Under nitrogen protection, 2,4-dichlorobenzofuran[3,2-D]pyrimidine (24 g, 0.1 mol), M3 (27 g, 0.1 mol), Pd(t-Bu 3 P) 2 (1.5g, 3mmol), potassium phosphate (64g, 0.3mol), toluene 200mL, stirring, the reaction solution was heated to reflux temperature, and the reaction was continued for 8h until the reaction was complete. The reaction solution was cooled to room temperature, filtered, the filtrate was washed with water, separated, the organic phase was dried, filtered and concentrated, and the residue was purified by silica gel column chromatography to obtain M13-1, with a yield of 33g, a yield of 71%, an HPLC content of 99%, and an LC-MS molecular weight of 470.1.

[0041] Step 2: Synthesis of M13: Operation process: The synthesis process of M13 refers to the synthesis process of M2. M13-1 (33 g, 0.07 mol) was added to obtain M13 with a yield of 29 g, a yield of 74%, a HPLC content of 99%, and a LC-MS molecular weight of 562.2.

[0042] Synthesis of intermediate M15:

[0043] Step 1: Synthesis of M15-1: Operation process: The synthesis process of M15 refers to the synthesis process of M9-1. 2,4-dichlorobenzofuran[3,2-D]pyrimidine (24 g, 0.1 mol) and M4 (27 g, 0.1 mol) were added to obtain M15-1 with a yield of 41 g, a yield of 76%, a HPLC content of 99%, and a molecular weight of 546.1 shown by LC-MS.

[0044] Step 2: Synthesis of M15: Operation process: The synthesis process of M15 refers to the synthesis process of M2. M15-1 (41 g, 0.08 mol) was added to obtain M15 with a yield of 36 g, a yield of 75%, a HPLC content of 99%, and a LC-MS molecular weight of 638.3.

[0045] The synthesis of other intermediates refers to the synthesis process of the above intermediates. Using the above important intermediates, the synthesis implementation process of the preferred compound 2 and compound 33 is exemplified as follows: Synthesis of compound 2:

[0046] Operation process: The synthesis process of compound 2 refers to the synthesis process of M9-1, and M5 (5.6 g, 0.01 mol) and deuterated chlorobenzene (1.2 g, 0.01 mol) are added to obtain compound 2 with a yield of 3.8 g, a yield of 73%, a HPLC content of 99%, and a molecular weight of 517.2 shown by LC-MS.

[0047] Synthesis of compound 33:

[0048] Operation process: The synthesis process of compound 33 refers to the synthesis process of M2-1, and M5-1 (2.7 g, 0.01 mol) and deuterated carbazole (21.8 g, 0.01 mol) are added to obtain compound 33 with a yield of 4.7 g, a yield of 77%, a HPLC content of 99%, and a molecular weight of 609.3 shown by LC-MS.

[0049] The synthesis of other compounds refers to the synthesis process of compound 2 and compound 33. The statistics of important starting materials involved in the present invention are shown in Table 2.

[0050] Table 2 Important starting materials involved in the present invention

[0051] like Figure 2~3 Shown are the NMR spectra of compound 2 and compound 33.

[0052] The process of the organic electroluminescent device embodiment is described as follows: Based on one of the above organic light-emitting compounds, a bipolar main light-emitting material used as a light-emitting layer in the test device, wherein the basic structure and preparation method of the device adopt conventional device preparation process technology, the device structure schematic diagram is shown in Figure 1 As shown, the method for making the test device is specifically described as follows: The schematic diagram of the test device structure of the experimental process of the present invention is as follows Figure 1 As shown: polymer substrate 1, anode layer 2 (ITO conductive glass), hole injection layer 3 material (HIL), hole transport layer 4 (HTL), electron blocking layer 5 (EBL), light emitting layer 6 (EML), hole blocking layer 7 (HBL), electron transport layer 8 (ETL), electron injection layer 9 (EIL), cathode layer 10 (Mg (10%) -Al (90%) alloy) and high refractive index cover layer 11, wherein the organic light emitting compound of the present invention is used in the light emitting layer (EML) and is used as a bipolar main light emitting material for the evaluation experiment process. The detailed device preparation process is briefly described as follows: A certain thickness of indium tin oxide is adhered to a polymer substrate with high mechanical strength, excellent thermal stability, excellent water resistance and excellent transparency as an anode. The polymer substrate is pretreated and cleaned in advance, and then different functional layers and organic functional layer materials of set thickness are sequentially evaporated according to the above structural characteristics. After the electron injection layer material is evaporated, a magnesium-aluminum alloy cathode is sputtered at a low temperature. After the cathode sputtering is completed, a layer of high refractive index covering layer material is evaporated to improve the refractive index of the cathode surface and increase the light extraction rate. Finally, the test device is packaged using conventional device test packaging methods to complete the entire production process of the test device.

[0053] Preferably, the anode is usually a material with a large work function in order to smoothly inject holes into the organic layer. The anode materials that can be used in the present invention include indium tin oxide (ITO), indium zinc oxide (IZO), tin dioxide (SnO 2 ), zinc oxide (ZnO), etc.

[0054] Preferably, the cathode is usually a material with a small work function in order to facilitate the injection of electrons into the organic layer. The cathode materials that can be used in the present invention include: magnesium (Mg), silver (Ag), aluminum (Al), aluminum-lithium (Al-Li), calcium (Ca), magnesium-indium (Mg-In), magnesium-aluminum (Mg-Al) and other metals or alloys and organic combinations thereof.

[0055] The organic functional layer is distributed between the cathode and the anode, and specifically includes a hole injection layer, a hole transport layer, an electron blocking layer, a light-emitting layer, a hole blocking layer, an electron transport layer, and an electron injection layer; the light-emitting layer is located between the electron blocking layer and the hole blocking layer, and other functional layer materials are selected from corresponding functional layer materials with excellent cost performance in the industry to prepare test devices. The compatibility between the functional layers needs to be determined through a series of tests and screening processes.

[0056] The functional organic layer can be formed on the electrode by vacuum thermal evaporation, spin coating, printing and other means or methods. The compounds used as each organic layer except the light-emitting layer can be organic small molecules, organic macromolecules and polymers, and combinations thereof.

[0057] The light-emitting layer (EML) is co-evaporated in the form of a composite of a host and a guest light-emitting material, the host light-emitting material is selected from the organic light-emitting compound of the present invention, and the guest light-emitting material is selected from the phosphorescent material. , In this case, the composite ratio of the two is 99.5:0.5; or the guest luminescent material is selected from a fluorescent material with excellent performance , , at this time, the composite ratio of the two is 98:2. After the functional layers are evaporated, they are finally packaged using the device packaging method commonly used in the industry. The samples used for test devices are prepared into 30mm×30mm samples, and then the luminous performance indicators of the above samples are tested. Compared with the test devices prepared by the commonly used main luminous materials, the test devices prepared by the preferred compounds of the present invention have better life when the luminous brightness is consistent, and higher brightness under the same test voltage.

[0058] The specific device preparation details are as follows: Device comparison examples 1~3: The organic electroluminescent device was prepared by following the steps below: like Figure 1 As shown, the polymer substrate 1 (polyethylene terephthalate (PET) plastic 1.5mm); the anode layer 2 (indium tin oxide ITO 0.15mm) is washed before use, that is, alkaline washing, pure water washing, drying, and then ultraviolet-ozone washing are performed in sequence to remove organic residues on the surface of the anode layer.

[0059] On the anode layer 2, MoO with a thickness of 20 nm was deposited. 3 As the hole injection layer 3 (HIL).

[0060] A hole transport layer 4 (HTL) with a thickness of 45 nm is evaporated on the hole injection layer 3, and the material is selected from HT-1, HT-2, and HT-3 (HT-3 is selected for this test).

[0061] An electron blocking layer 5 (EBL) with a thickness of 30 nm is evaporated on the hole transport layer 4, and the material is selected from one of EB-1, EB-2, and EB-3 (EB-3 is selected in this case).

[0062] A light-emitting layer 6 (EML) with a thickness of 60 nm is evaporated on the electron blocking layer 5, wherein the main light-emitting material in the light-emitting layer is selected from one of H1, H2, and H3, and the guest light-emitting material is selected from one of the fluorescent materials Rubrene (Comparative Example 1) and TBPE (Comparative Example 2), and the main light-emitting material and the guest light-emitting material are composite co-evaporated at a mass ratio of 98:2; or the guest light-emitting material is selected from one of the phosphorescent materials DP-1, DP-2, and DP-3 (DP-1 is selected in this case, Comparative Example 3), and the main light-emitting material and the guest light-emitting material are composite co-evaporated at a mass ratio of 99.5:0.5.

[0063] A hole blocking layer 7 (HBL) with a thickness of 10 nm is evaporated on the light-emitting layer 6, and the material is selected from one of HB-1 and HB-2 (HB-1 is selected in this case).

[0064] A 30 nm thick electron transport layer 8 (ETL) is evaporated on the hole blocking layer 7, and the material is selected from one of ET-1, ET-2, and ET-3 (ET-2 is selected in this case).

[0065] A 16 nm electron injection layer 9 (EIL) is evaporated on the electron transport layer 8, and the material used is LiF.

[0066] After the electron injection layer 9 is evaporated, a 10 nm thick Mg—Al (Mg: Al=1: 9) alloy is sputtered as the cathode 10 by low-temperature sputtering.

[0067] Finally, a 40 nm thick covering layer 11 is evaporated on the cathode 10, and the material selected is CPL.

[0068] Finally, the above functional layers are vacuum packaged and the device is completed.

[0069] Detailed preparation scheme of device comparative examples 1 to 3: Comparative Example 1: PET substrate / ITO / MoO 3 (20nm) / HT-3(45nm) / EB-3(30nm) / H1:Rubrene =98:2(60nm) / HB-1(10nm) / ET-2(30nm) / LiF(16nm) / Mg: Al=1: 9 (10nm) / CPL (40nm); Comparative Example 2: PET substrate / ITO / MoO 3(20nm) / HT-3(45nm) / EB-3(30nm) / H1:TBPE =98:2(60nm) / HB-1(10nm) / ET-2 (30nm) / LiF(16nm) / Mg: Al=1: 9 (10nm) / CPL(40 nm); Comparative Example 3: PET substrate / ITO / MoO 3 (20nm) / HT-3(45nm) / EB-3(30nm) / H1:DP-1 =99.5:0.5(60nm) / HB-1(10nm) / ET-2 (30nm) / LiF(16nm) / Mg: Al=1: 9 (10nm) / CPL (40nm); Detailed preparation scheme of the embodiment of the present invention: Embodiment 1~embodiment 4: The device preparation process is carried out according to the method of device comparative example 1, except that the preferred compounds 1, 32, 80, and 112 of the present invention are used as the main luminescent material of the luminescent layer, and the guest luminescent material used in combination is Rubrene.

[0070] Embodiment 5~embodiment 10: The device preparation process is carried out according to the method of device comparative example 3, except that the preferred compounds 32, 80, 112, 34, 82, and 114 described in the present invention are used as the main luminescent materials of the luminescent layer, and the guest luminescent material used in combination is DP-1.

[0071] The functional layer materials involved in the above device preparation process can be selected from one or more combinations of corresponding related functional layer materials. During the device implementation process, the specific functional layer structures are introduced as follows: In the comparative example, the main luminescent material is selected from the following materials:

[0072] The HTL functional layer can be selected from the following materials:

[0073] The EBL functional layer is selected from the following materials:

[0074] The HBL functional layer materials are as follows:

[0075] The ETL functional layer materials are as follows:

[0076] The covering material is selected from the following materials:

[0077] The performance test data statistics of the test device and the control device prepared using the preferred compound of the present invention are shown in Table 3: Table 3

[0078] As shown in Table 3 above, from the test data of the entire device, under the same device manufacturing process conditions, at the same current density (20mA / cm 2 ) conditions, the device performance was tested under 40% RH and 25% RH conditions. The test device prepared by using the preferred compound of the present invention as the bipolar main light-emitting material had a significantly reduced roll-off efficiency, an increase of about 40% in current efficiency, an increase of about 45% in LT95 life, and an increase of about 45% in external quantum efficiency. This indicates that using the preferred compound of the present invention as the bipolar main material for the light-emitting layer of an OLED device can significantly improve the comprehensive light-emitting performance of the device.

[0079] Examples 1 to 7 show that the organic light-emitting compound of the present invention is used as a bipolar host material and is suitable for both fluorescent guest materials and phosphorescent guest materials.

[0080] Compared with Examples 5 to 7, Examples 8 to 10 show that the luminescence performance of the devices in Examples 8 to 10 is also greatly improved, which may be because the compounds corresponding to the host materials in Examples 8 to 10 (Compound 34, Compound 82, Compound 114) all contain multiple tert-butyl-substituted carbazole structures. The tert-butyl group is a bulky substituent that can prevent the formation of excimers caused by intramolecular attraction, thereby improving the luminescence efficiency.

[0081] The organic light-emitting compound of the present invention is used as a bipolar host material in the light-emitting layer of an OLED device, which can effectively balance the transmission of carriers, thereby making the excitons evenly distributed, avoiding the recombination of carriers at the interface, and reducing the quenching of triplet-triplet states under high exciton concentrations. In addition, the organic functional layer based on the bipolar material can make the device structure simple.

[0082] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.

[0083] Many other changes and modifications may be made without departing from the concept and scope of the present invention.It should be understood that the present invention is not limited to the specific embodiments, and the scope of the present invention is defined by the appended claims.

Claims

1. An organic light-emitting compound, characterized in that: The organic light-emitting compound has a structure as shown in Formula 1: ; Wherein: X1, X2, X3, and X4 are each independently selected from N atoms or C atoms and satisfy the following conditions: When X1 and X3 are both N atoms, X2 and X4 must be C atoms; When X2 and X4 are both N atoms, X1 and X3 must be C atoms; When X1 and X3 are not N atoms at the same time or when X2 and X4 are not N atoms at the same time, the combination of X1, X2, X3, and X4 is any combination of N atoms and C atoms; Y is selected from an O atom or a S atom; R1 and R3 are each independently selected from any one of C6-C12 aromatic groups, and the bonding mode of R1, R3 and the main structure is a ring, and the aromatic groups in R1 and R3 are monocyclic aromatic groups or polycyclic aromatic groups; R2 is selected from any one of a C6-C30 aryl group and a C4-C30 heteroaryl group, and the bonding mode between R2 and the main structure is a single bond; the heteroaryl group in R2 includes a monocyclic heteroaryl group, a polycyclic heteroaryl group or a condensed-ring heteroaryl group, and the heteroatom in the heteroaryl group includes an O atom, a S atom or a N atom; n is selected from 0, 1, 2 or 3.

2. An organic light-emitting compound according to claim 1, characterized in that: The R2 is selected from the following groups L1~L 42 or any of its derivatives: , , , , in, It is the bonding position between R2 and the main structure.

3. An organic light-emitting compound according to claim 2, characterized in that: The organic light-emitting compound is any one of the following compounds 1 to 224, and the specific structural formula is as follows: 。 4. An organic electroluminescent device, characterized in that: The organic electroluminescent device comprises a cathode, an anode and an organic layer located between the cathode and the anode, the organic layer comprises a hole transport layer, a light-emitting layer and an electron transport layer, the light-emitting layer comprises a host light-emitting material and a guest light-emitting material, and the host light-emitting material comprises any one or a combination of two of the organic light-emitting compounds described in claim 3.

5. An electroluminescent device according to claim 4, characterized in that: The guest luminescent material can be selected from phosphorescent materials with excellent performance , and the mass fraction of the guest luminescent material in the entire luminescent layer is between 0.1% and 3.0%.

6. An electroluminescent device according to claim 4, characterized in that: The guest luminescent material can also be selected from fluorescent materials with excellent performance. , and the mass fraction of the guest luminescent material in the entire luminescent layer is between 0.5% and 5.0%.

7. The organic electroluminescent device according to claim 4, characterized in that: The organic electroluminescent device is applied to the fields of luminous illumination, image display or photoelectric signal transmission.

Citation Information

Patent Citations

  • Compound and organic light emitting diode comprising same

    CN111868048A

  • 8H-dibenzacridine derivative and electroluminescent device thereof

    CN118754883A

  • Organic light compound and organic light device using the same

    KR1020130007390A

  • Organic electroluminescent device and manufacturing method thereof

    US20190165286A1

  • Organic compound, electronic component, and electronic device

    WO2022267839A1